Screening of Analgesic, Antimicrobial, Cytotoxic and Antioxidant Activities of Metal Complexes of Indomethacin (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The present study was performed to evaluate the biological activities of metal complexes of indomethacin with cobalt, copper, manganese and zinc. In radiant tail flick method, complexes of indomethacin with cobalt and copper at a dose of 20 mg/kg b.w. showed significant central analgesic activity having 66.09% and 75.45% elongation of time after 30 minutes and complexes of indomethacin with copper at a dose of 20 mg/kg b.w. showed significant central analgesic activity having 62.47% elongation of time after 60 minutes compared to the standard morphine. In this study, indomethacin and its complexes with cobalt, copper and manganese showed mild antimicrobial activity and the indomethacin-manganese complex also displayed highest cytotoxicity with a lowest LC50 1.222 ± 0.21 ?g/ml and indomethacin-cobalt, indomethacin-copper and indomethacin-zinc had significant LC50 of 1.549 ± 0.39 ?g/ml, 1.662 ± 0.17 ?g/ml and 1.903 ± 0.64 ?g/ml, respectively where standard vincristine sulphate had LC50 of 0.824 ± 0.04 ?g/ml. The complex of indomethacin with cobalt, copper, manganese and zinc revealed % of inhibition 38.46 ± 1.03, 64.31 ± 0.21, 46.71 ± 0.46 and 30.79 ± 0.30, respectively and also had significant IC50 of 17.51 ± 0.62 ?g/ml, 12.31 ± 0.58 ?g/ml, 15.71 ± 0.16 ?g/ml and 19.84 ± 0.08 ?g/ml correspondingly. This study indicates that the complexes of indomethacin had analgesic, antimicrobial, cytotoxic and antioxidant activities which could be subjected for further therapeutic evaluation. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21895 Dhaka Univ. J. Pharm. Sci. 13(2): 175-180, 2014 (December)